Modernity and Identity processes on the light of the diffusion of new digital technologies - Parente , Giuliana (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
This paper delves into the complex interplay among identity processes, modern society, and new media. Drawing from sociological theories, it commences with an examination of identity evolution in modern industrial societies, accentuating the proliferation of roles and statuses. The advent of digital technologies introduces complexity to individual choices, nurturing a malleable identity. The narrative then pivots to the transformative influence of Information and Communication Technologies (ICT), ushering in a global village. The emergence of Web 2.0 and 3.0 signifies pivotal updates, fostering user-generated content and reshaping societal interactions. The ongoing shifts in socialization processes due to economic, political, and cultural changes are scrutinized, with a spotlight on the instrumental role of digital media. The intricate process of identity formation amidst evolving socialization is explored, underscoring the morphostatic and morphogenetic functions of media. The interconnected nature of online and offline identity processes is dissected, emphasizing their symbiotic communication and coexistence. In conclusion, the paper underscores the seamless exchange between online and offline identities facilitated by the portability of devices. The overarching goal of this contribution is to provide a nuanced understanding of identity dynamics, weaving together insights from sociological theories and technological developments.